The spy next door - Cheng, Long, 1954-; Valletta, Amber, 1974-; Cyrus, Billy Ray, 1961-; Lopez, George, 1961-; Lions Gate Home Entertainment (Santa Monica, CA : Lions Gate Entertainment, 2010)
Bob Ho is an undercover CIA superspy who decides to give up his career in espionage to settle down with his next-door neighbor and girlfriend, Gillian. But Bob has one more mission to complete before Gillian agrees to marry him; he has to win over her three opinionated kids. When Gillian suddenly has to leave town, Bob volunteers to babysit the children so he can earn their approval.
DVD, widescreen.
English dialogue; English or Spanish subtitles. Closed-captioned.
Jackie Chan, Amber Valletta, Billy Ray Cyrus, George Lopez.
Rating: PG; for sequences of action violence and some mild rude humor.
Keywords: Spies -- Drama; Espa̕s -- Teatro